Membrane Distillation Technology Using for Desalination of Associated Oil Water Production and Study Efficiency of Feed Water Operation Parameter on Air Gap Membrane Distillation Process Production - Alfaez, Safaa A. (Journal of Petroleum Research and Studies, 2022)
In this study; membrane distillation technology using to associated oil water production desalination by air gap membrane distillation unit to removed salt from the water after separating oil product, via PTEF commercial hydrophobic membrane distillation with 0.22 µm porous and 0.011 m contact surface area, evaluated the desalination system and operation parameter for feed water effected on process production by employment the distillation under boiling point temperature that getting commercial increments and study the energy gain by calculating the GOR of the desalination process. The study focusing on the air gap membrane distillation desalination process by a range of temperature after primary simple sedimentation and filtration it’s obtained salt rejection up to 98.9% that proves process separation efficiency. Evaluated the mean operation parameters of feed water affected on permeate water production when selected the feed temperature and flow rate with fixed coolant temperature, coolant flow rate, and air gap width to get an optimum range for feed water operation parameter to obtain optimum value to permeate water production and saving energy.